Cyclooxygenase-2 and human epidermal growth factor receptor type 2 (HER-2) expression simultaneously in invasive and in situ breast ductal carcinoma - Lucarelli, Adrienne Pratti (2011)
CONTEXT AND OBJECTIVE: Cyclooxygenase-2 (COX-2) and human epidermal growth factor receptor type 2 (HER-2) are associated with tumorigenesis. Studies have shown that HER-2 can regulate COX-2 expression. The aim of this study was to evaluate the correlation between COX-2 and HER-2 expression in normal breast epithelium and in ductal carcinoma in situ (DCIS) and invasive ductal carcinoma (IDC) present in the same breast. DESIGN AND SETTING: Cross-sectional study at the Mastology Unit of the Department of Gynecology and Obstetrics, Santa Casa de Misericórdia de São Paulo Hospital. METHODS: COX-2 and HER-2 were detected using immunohistochemistry on 100 tissue fragments. HER-2 ≥ +2 was subjected to fluorescence in situ hybridization (FISH). RESULTS: COX-2 expression was detected in 87%, 85% and 75% of IDC, DCIS and normal epithelium, respectively. HER-2 expression was detected in 34% of IDC and 34% of DCIS. COX-2 in DCIS correlated with HER-2 in IDC (P = 0.049) and DCIS (P = 0.049). COX-2 in normal epithelium correlated with HER-2 in IDC (P = 0.046) and DCIS (P = 0.046). COX-2 in IDC was not associated with HER-2 (P = 0.235). Comparison between COX-2 and HER-2 in DCIS showed that there was a statistically significant difference with regard to nuclear grades II and III and presence of comedonecrosis (P < 0.001). In IDC, there was significant expression with nuclear grades II and III and histological grade II (P < 0.001). CONCLUSIONS: Our findings provide evidence that HER-2 and COX-2 regulate each other.